2009
DOI: 10.1038/mt.2008.269
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency Transduction of the Mouse Retina by Tyrosine-mutant AAV Serotype Vectors

Abstract: Vectors derived from adeno-associated viruses (AAVs) have become important gene delivery tools for the treatment of many inherited ocular diseases in well-characterized animal models. Previous studies have determined that the viral capsid plays an essential role in the cellular tropism and efficiency of transgene expression. Recently, it was shown that phosphorylation of surface-exposed tyrosine residues from AAV2 capsid targets the viral particles for ubiquitination and proteasome- mediated degradation, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
346
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(360 citation statements)
references
References 47 publications
10
346
1
3
Order By: Relevance
“…In response to axonal injury, 50%-75% of RGCs die by 2 wks (31). Mice carrying a floxed allele of Dlk (Dlk fl/fl ) were injected intravitreally with a self-complementary, capsid-modified adeno-associated virus 2 (AAV2) (32,33) expressing Cre. Injection of the AAV2-Cre resulted in Cre expression in nearly 100% of RGCs ( Fig.…”
Section: Dlk Inhibition Promotes Rgc Survival In Vivo After Optic Nervementioning
confidence: 99%
“…In response to axonal injury, 50%-75% of RGCs die by 2 wks (31). Mice carrying a floxed allele of Dlk (Dlk fl/fl ) were injected intravitreally with a self-complementary, capsid-modified adeno-associated virus 2 (AAV2) (32,33) expressing Cre. Injection of the AAV2-Cre resulted in Cre expression in nearly 100% of RGCs ( Fig.…”
Section: Dlk Inhibition Promotes Rgc Survival In Vivo After Optic Nervementioning
confidence: 99%
“…Consistent with this hypothesis, they observed that site-directed mutagenesis of surface-exposed tyrosine residues significantly improve the transduction efficiency of AAV vectors (about 10-fold increase) in human epithelial cells in vitro. It has also been demonstrated that tyrosine mutant AAV vectors display enhanced gene delivery efficiencies in vivo when compared to wild-type AAV vectors [40] . Although further investigation is warranted, such enhanced AAV vectors engineered through rational design to avoid cytoplasmic degradation could also potentially enhance the efficiencies of AAV-mediated gene targeting in human stem cells.…”
Section: Molecular Engineering Of Viral Vectorsmentioning
confidence: 99%
“…A further development of AAV as a vector for photoreceptor cell gene targeting has involved mutagenesis of the viral capsid proteins to increase the efficiency of transduction and penetration of the vector across the layers of the neurosensory retina. Mutagenesis of specific capsid tyrosine residues can enable efficient transduction of photoreceptors following intravitreal injection, 28,29 a technique that is safer and technically less challenging than subretinal injection. However, administration of AAV vectors into the vitreous can stimulate more powerful immune responses than are typically evident following administration into the subretinal space, which has the benefit of relative immune privilege.…”
Section: Gene Transfer To Photoreceptor Cellsmentioning
confidence: 99%